1992
DOI: 10.1111/j.1540-8159.1992.tb03098.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Abnormalities of the Atrial Muscle in Patients with Manifest Wolff‐Parkinson‐White Syndrome Associated with Paroxysmal Atrial Fibrillation

Abstract: We investigated the electrophysiological properties of the atrial muscle in 33 patients with manifest Wolff-Parkinson-White syndrome. Group I consisted of 13 patients with paroxysmal atrial fibrillation and group II consisted of 20 patients without paroxysmal atrial fibrillation. The anterograde and retrograde effective refractory periods of the accessory pathway and the inducibility of atrioventricular reciprocating tachycardia were not significantly different between the two groups. Endocardial electrograms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
0
27
1
1
Order By: Relevance
“…This finding was similar to the previous study; there is no relationship between the AF formation and the ERP of AP. 9,10,15,17 Due to the advancement of the RFCA technique in the past decade, many cardiac arrhythmias in children have become curable. However, the management for asymptomatic children with WPW syndrome is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was similar to the previous study; there is no relationship between the AF formation and the ERP of AP. 9,10,15,17 Due to the advancement of the RFCA technique in the past decade, many cardiac arrhythmias in children have become curable. However, the management for asymptomatic children with WPW syndrome is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The manifest WPW syndrome children with AF (group 1; n = 11) consisted of seven male and four female children (mean age 15 ± 3 years, range [10][11][12][13][14][15][16][17][18]. The study excluded the patient who had Ebstein's anomaly associated with moderate tricuspid regurgitation and right atrial enlargement.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…We have previously shown that these indices of atrial vulnerability were greater in patients with hyperthyroidism and PAF than in control subjects [19,20]. The greater atrial IACD and shorter atrial ERP resulted in shortening of the atrial wavelength, which predisposed to development of PAF [19][20][21][22]. The mean atrial ERP in patients with hyperthyroidism (187±7 ms) was significantly shorter than that of controls (215±29 ms, p<0.01).…”
mentioning
confidence: 95%
“…The WPW patients with AF have intrinsic atrial muscle abnormalities and most of them present abnormally prolonged and fractionated atrial electrograms that are recorded with atrial endocardial catheter mapping during sinus rhythm . 14 The role of an atrial firing focus as a trigger for AF initiation in the WPW syndrome is not well documented yet. AF can also be initiated by ectopic beats originating from the pulmonary veins, and elsewhere.…”
Section: Journal Of Atrial Fibrillationmentioning
confidence: 99%
“…13 Several mechanisms responsible for the development of AF in the WPW syndrome were investigated in detail, namely, the spontaneous degeneration of AVRT into AF, the electrical properties of the AP, the effects of AP on atrial architecture, and the intrinsic atrial muscle vulnerability. [14][15][16][17][18][19][20][21][22] Considering all the mechanisms proposed to explain the development of atrial fibrillation in the WPW syndrome, this review analizes the available data on this singular and interesting topic since AF has a reserved prognostic significance in patients with the WPW syndrome, and has an unusually high incidence in the absence of any clinical evidence of organic heart disease.…”
mentioning
confidence: 99%